An image sensor with an in-pixel demodulation function for detecting the intensity of a modulated light signal. - Ohta, J. (IEEE Transactions on electron devices)
An image sensor with an in-pixel demodulation function for detecting modulated light is proposed and demonstrated. The pixel has two floating diffusion regions, one of which stores charges produced by static illumination, and the other stores charges produced by both static and modulated illumination. By subtracting the two outputs, images produced only by the modulated illumination can be obtained. Based on the proposed circuit, an image sensor with 64 × 64 pixels is fabricated using a 0.6 μm two-poly three-metal CMOS technology. Using this sensor, we successfully demonstrate the extraction of the modulated component of images under constant illumination conditions. In addition, for the application of motion capture, we demonstrate that a marker, which is a modulated light source, can be extracted from a captured image under several light conditions by using this sensor. Finally, means of improving the characteristics of charge transfer efficiency are discussed.